2000
DOI: 10.3354/cr014025
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of salinity and oxygen concentrations in the Baltic Sea on large-scale atmospheric circulation

Abstract: ABSTRACT:The relationship between the low-frequency (annually averaged) salinity and oxygen concentrations in the last 30 yr in the Baltic Sea and the large-scale atmospheric circulation was statistically analyzed. It was found that at these time scales the evolution of salinity and oxygen is quite homogeneous in depth, i.e. deviations from the long-term mean tend to be of the same sign in the upper and deeper layers simultaneously. Moreover, the evolution of the salinity and oxygen concentrations are negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 25 publications
4
36
0
1
Order By: Relevance
“…This produces a barotropic pressure gradient and hampers the flow of high-saline water through the Danish Straits into the Baltic proper . A similar long-term sensitivity for stronger westerly winds for the Baltic Sea was shown by Zorita and Laine (2000).…”
Section: Evolution Of Water Temperature Sea Ice and Salinitysupporting
confidence: 52%
“…This produces a barotropic pressure gradient and hampers the flow of high-saline water through the Danish Straits into the Baltic proper . A similar long-term sensitivity for stronger westerly winds for the Baltic Sea was shown by Zorita and Laine (2000).…”
Section: Evolution Of Water Temperature Sea Ice and Salinitysupporting
confidence: 52%
“…A strong meridional sea level pressure gradient over the North Atlantic causes positive rain fall anomalies, increasing river runoff and decreasing salinity. Due to the weakened stratification, deep water oxygen concentrations increase (Gerlach 1994;Zorita and Laine 2000). An increase in precipitation will also result in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity and oxygen concentration in the Baltic Sea also depend strongly on large-scale atmospheric circulation (Zorita and Laine 2000). A strong meridional sea level pressure gradient over the North Atlantic causes positive rain fall anomalies, increasing river runoff and decreasing salinity.…”
Section: Introductionmentioning
confidence: 99%
“…In the Bornholm Basin, deep temperature observations reveal waters of warm and cold inflows ) that can be later traced in the In the Gulf of Finland, a sub-region with a free connection to the Baltic Proper and the highest freshwater discharge per unit sea volume, changes in salinity and stratification generally follow those of the Baltic Proper, but are not fully synchronous (e.g. Zorita and Laine 2000). On the basis of monitoring data for the period 1965-2000, Laine et al (2007) found a continuous decrease in salinity and density stratification until the early 1990s, after which there was a slight increase.…”
Section: 3mentioning
confidence: 99%